An Unconditionally Stable Method for Solving the Acoustic Wave Equation. (11th August 2015) - Fu, Zhi-Kai; Shi, Li-Hua; Huang, Zheng-Yu; Fu, Shang-Chen
Abstract : An unconditionally stable method for solving the time-domain acoustic wave equation using Associated Hermit orthogonal functions is proposed. The second-order time derivatives in acoustic wave equation are expanded by these orthogonal basis functions. By applying Galerkin temporal testing procedure, the time variable can be eliminated from the calculations. The restriction of Courant-Friedrichs-Levy (CFL) condition in selecting time step for analyzing thin layer can be avoided. Numerical results show the accuracy and the efficiency of the proposed method.